Associations between blood cultures after surgery for colorectal cancer and long‐term oncological outcomes. Issue 3 (22nd November 2019) - Watt, S. K.; Fransgaard, T.; Degett, T. H.; Thygesen, L. C.; Benfield, T.; Knudsen, J. D.; Fuursted, K.; Jensen, T. G.; Dessau, R. B.; Schønheyder, H. C.; Møller, J. K.; Gögenur, I.
Abstract : Background: Systemic inflammation following curative surgery for colorectal cancer may be associated with increased risk of recurrence. [Correction added on 29 November 2019, after first online publication: text amended for accuracy.] This study investigated whether a clinically suspected infection, for which blood cultures were sent within 30 days after surgery for colorectal cancer, was associated with long‐term oncological outcomes. Methods: This register‐based national cohort study included all Danish residents undergoing surgery with curative intent for colorectal cancer between January 2003 and December 2013. Patients who developed recurrence or died within 180 days after surgery were not included. Associations between blood cultures taken within 30 days after primary surgery and overall survival, disease‐free survival and recurrence‐free survival were analysed using Cox regression models adjusted for relevant clinical confounders, including demographic data, cancer stage, co‐morbidity, blood transfusion, postoperative complications and adjuvant chemotherapy. Results: The study included 21 349 patients, of whom 3390 (15·9 per cent) had blood cultures taken within 30 days after surgery. Median follow‐up was 5·6 years. Patients who had blood cultures taken had an increased risk of all‐cause mortality (hazard ratio (HR) 1·27, 95 per cent c.i. 1·20 to 1·35; P < 0·001), poorer disease‐free survival (HR 1·22, 1·16 to 1·29; P < 0·001) and higher risk of recurrence (HR 1·15, 1·07 to 1·23; P < 0·001) than patients who did not have blood cultures taken. Conclusion: A clinically suspected infection requiring blood cultures within 30 days of surgery for colorectal cancer was associated with poorer oncological outcomes. Abstract : In a register‐based study of 21 349 patients who survived more than 180 days after curative surgery for colorectal cancer, having blood cultures taken within 30 days after surgery was associated with higher all‐cause mortality, poorer disease‐free survival and higher risk of recurrence. Systemic inflammatory response? Abstract : Antecedentes: La inflamación sistémica en el cáncer colorrectal puede asociarse con un aumento del riesgo de recidiva. En este estudio se investigó si la sospecha clínica de infección, en la que se obtuvieron cultivos de sangre periférica durante los primeros 30 días de la cirugía por cáncer colorrectal, se asociaba con los resultados oncológicos a largo plazo. Métodos: Se trata de un estudio de cohortes de un registro de una base de datos nacional, que incluyía todos los sujetos residentes en Dinamarca sometidos a cirugía por cáncer colorrectal con intención curativa desde enero de 2003 a diciembre de 2013. Los pacientes con recidiva o que fallecieron durante los primeros 180 días después de la cirugía fueron excluidos. Se estimaron las asociaciones entre los cultivos de sangre periférica efectuados en los primeros 30 días tras la cirugía primaria y la supervivencia global, supervivencia libre de enfermedad y supervivencia libre de recidiva mediante modelos de regresión de Cox, ajustados por variables clínicas confusoras relevantes (incluyendo datos demográficos, estadio del cáncer, comorbilidad, transfusión de sangre, complicaciones postoperatorias y quimioterapia adyuvante). Resultados: El estudio incluyó 21.349 pacientes, de los cuales en 3.390 (16%) se habían obtenido cultivos de sangre periférica durante los primeros 30 días tras la cirugía. La mediana de seguimiento fue de 5, 6 años. Los pacientes en los que se había obtenido cultivos de sangre periférica presentaron un riesgo aumentado de mortalidad por cualquier causa (cociente de riesgos instantáneos, hazard ratio, HR 1, 27, i.c. del 95% 1, 20‐1, 35; P < 0.0001), peor supervivencia libre de enfermedad (HR 1, 22, i.c. del 95% 1, 16‐1, 29; P < 0, 0001) y mayor riesgo de recidiva (HR 1, 15, i.c. del 95% 1, 07‐1, 23; P < 0, 0001) que los pacientes en los que no se habían obtenido cultivos. Conclusión: La presencia de una infección sospechada clínicamente para la cual se requiere obtener cultivos de sangre periférica en los primeros 30 días tras cirugía por cancer colorrectal se asoció con peores resultados oncológicos.